Redescription of Lepidocyrtus peisonis Traser & Christian, 1992 with notes on Lepidocyrtus mariani Traser & Dányi, 2008 (Collembola: Entomobryidae) - Winkler, Daniel; Mateos, Eduardo (Zootaxa, 2018)
Two species of Lepidocyrtus Bourlet have been studied. L. peisonis Traser & Christian, 1992 has been redescribed based on the type material and newly collected specimens. This species is characterized by dorsal macrochaetae formula R0R1sR1R2So/00/0101+3, truncate unguiculi and a newly observed character missing in the original description: a lateral tuft of long filiform chaetae on abd. III, never described for any European species of subgenera Lanocyrtus and Lepidocyrtus s.str. L. mariani Traser & Dányi, 2008 has been revised based on the holotype and recently collected specimens. L. mariani is defined by the dorsal macrochaetae formula R0R1sR1So/00/0101+3 and the presence of small pseudopori on the apical membranous area of antennal segments, lateral region of th. III–abd. IV and dorsal surface of dens.